2023
DOI: 10.1259/bjr.20220852
|View full text |Cite
|
Sign up to set email alerts
|

Prostate stereotactic body radiotherapy: quantifying intra-fraction motion and calculating margins using the new BIR geometric uncertainties in daily online IGRT recommendations

Abstract: Objectives: To measure the magnitude of intra fraction prostate motion (IFPM) during stereotactic radiotherapy (SBRT) delivered without intrafraction tracking. To assess if current margins adequately cover IFPM. To derive margins using new guidelines Methods: IFPM was determined in 20 patients receiving 36.25 Gy in 5 fractions using 97 pairs of pre and post treatment cone beam CT (CBCT) scans. Correlation of time between CBCT acquisitions and motion was determined. The magnitude of IFM was compared to current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Similar prostate displacements were found in other studies [34] , [35] , which highlighted that any reduction in overall treatment time could be beneficial for patients as reduces treatment uncertainties resulting from intrafractional motion. McNeice et al [35] showed that the PTV margins used in our work (6/3 mm) adequately account for most of intrafraction motion.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar prostate displacements were found in other studies [34] , [35] , which highlighted that any reduction in overall treatment time could be beneficial for patients as reduces treatment uncertainties resulting from intrafractional motion. McNeice et al [35] showed that the PTV margins used in our work (6/3 mm) adequately account for most of intrafraction motion.…”
Section: Discussionsupporting
confidence: 85%
“…However, this would require the analysis of the contribution to margins of other sources of errors, e.g. delineation errors [35] , and will be investigated separately in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…While slight target displacements during normo-fractionated treatments are generally tolerable because they occur randomly and average out during the treatment course, their impact becomes more critical in SBRT due to potential long-term effects and reduced statistical averaging of errors. Moreover, in high-dose-per-fraction treatments, it is important to balance any potential margins’ expansion against the risk of increased toxicity, especially if current practices are yielding favorable biochemical control and side effects [ 27 ]. Therefore, intrafraction motion management and real-time monitoring have emerged as strategies to ensure accurate radiation delivery and minimize adverse effects but with considerable and continuous investment of resources and time.…”
Section: Introductionmentioning
confidence: 99%